Reconfiguration strategy for fully actuated translational cable-suspended parallel robots - Bettega, Jason; Boschetti, Giovanni; Piva, Giulio; Richiedei, Dario; Trevisani, Alberto (Frontiers in Robotics and AI, 2023)
Cable-Suspended Parallel Robots (CSPRs) are a class of Cable-Driven Parallel Robots (CDPRs) for which cable tension is created by gravity. In CSPRs, reconfigurability, i.e., the possibility of modifying the position of the cable connection points on the base frame, is particularly interesting to investigate, since it paves the way for future industrial and service applications of CSPRs, where the base frame can also be replaced by mobile agents. This report focuses on Translational Reconfigurable CSPRs (TR-CSPRs), i.e., reconfigurable CSPRs with a point mass end-effector driven by at least three cables. The objective of the work is twofold. First it is proved that the Wrench Exertion Capability (WEC) performance index can be usefully exploited to identify the configurations of the cable connection points optimizing a task-related performance. Then, by referring to the case of a three-cable TR-CSPR with a single reconfigurable connection point and in quasi-static working condition, an analytical approach is provided to reconfigure the robot while executing a task in order to avoid one of the paramount problems of cable robots: cable slackness. Brought together, the two contributions allow defining a reconfiguration strategy for TR-CSPRs. The strategy is presented by applying it to a numerical example referring to a TR-CSPR used for lifting and moving a load along a prescribed path. First, the use of the WEC allows predicting if robot reconfigurability makes it possible to pass quasi-statically along all the points of a given path; then reconfigurability is also exploited to avoid cable slackness along the path.